2020
DOI: 10.1200/jco.19.00457
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib in Patients With Epidermal Growth Factor Receptor Mutation–Positive Non–Small-Cell Lung Cancer and Leptomeningeal Metastases: The BLOOM Study

Abstract: PURPOSE In this phase I study (BLOOM), osimertinib, a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), was evaluated in patients with leptomeningeal metastases (LMs) from EGFR-mutated (EGFRm) advanced non–small-cell lung cancer (NSCLC) whose disease had progressed on previous EGFR-TKI therapy. PATIENTS AND METHODS Patients with cytologically confirmed LM received osimertinib 160 mg once daily. Objectives were to assess confirmed objective response rate (ORR), duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
225
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(236 citation statements)
references
References 40 publications
10
225
0
1
Order By: Relevance
“…In the BLOOM study, LM ORR was 62%, and the median systemic PFS and OS were 8.6 and 11.0 months, respectively. 23 In this study, there was no apparent correlation between LM response and previous WBRT, consistent with that reported in the BLOOM study. 23 The AURA studies only allowed the inclusion of patients with WHO performance status 0 or 1 and asymptomatic CNS metastases (including LMs).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the BLOOM study, LM ORR was 62%, and the median systemic PFS and OS were 8.6 and 11.0 months, respectively. 23 In this study, there was no apparent correlation between LM response and previous WBRT, consistent with that reported in the BLOOM study. 23 The AURA studies only allowed the inclusion of patients with WHO performance status 0 or 1 and asymptomatic CNS metastases (including LMs).…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between changes from the baseline in non-CNS tumor size and LM responses at each visit was explored graphically. Data from patients included in the AURA LM analysis (treated with osimertinib [80 mg qd]) and the BLOOM study (treated with osimertinib [160 mg qd]) 23 were used in this comparative analysis. Only patients who provided a percentage change from baseline measurement and postbaseline LM response were included in the comparison.…”
Section: Graphical Comparison Of Lm Response and Longitudinal Non-cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Patients with poor performance status and diffuse LMD might be better served by supportive care alone rather than an intervention, and providing these patients with a reasonable estimate of their prognosisd which depends on accurate characterization of the nature of their LMDdwould be essential for them to make an informed decision on care. Conversely, identification of nLMD would suggest consideration of focal SRS to these lesions, 6,7 perhaps along with novel systemic treatments, [9][10][11] though the optimal treatment is far from established. Developing and implementing more efficacious and less morbid approaches to the treatment of both diffuse and discrete LMD will require well-designed and thoughtfully analyzed clinical trials.…”
mentioning
confidence: 99%
“…Yang et al (2020) reported an ORR of 62% with a median DoR of 15.2 months. 135 Osimertinib further led to an improvement of neurological symptoms and CSF clearance in 57% and 28% of the patients, respectively. 135 Notably, the median OS of 11.0 months slightly surpassed historical reported results.…”
Section: Efficacy Of Egfr-tkis In Brain Metastases and Leptomeningealmentioning
confidence: 96%